Fine structure of the doublet P levels of boron - Saeed Nasiri; Dmitry Tumakov; Monika Stanke; Andrzej Kędziorski; Ludwik Adamowicz; Sergiy Bubin (Physical Review Research)
We report high-accuracy calculations of the ground and the lowest eight excited ^{2}P^{o} states of the two stable isotopes of the boron atom, ^{10}B and ^{11}B, as well as of the boron atom with an infinite nuclear mass ^{∞}B. The nonrelativistic wave function of each of the states is generated in an independent variational calculation by expanding it in terms of a large number, 12000–17000, of all-electron explicitly correlated Gaussian (ECG) functions whose nonlinear parameters are extensively optimized with a procedure that employs analytic energy gradient determined with respect to these parameters. These highly accurate wave functions are used to compute the fine-structure splittings using the first order of the perturbation theory (∼α^{2}), where α is the fine-structure constant, which are then corrected for the electron magnetic moment anomaly (∼α^{3}). As the nonrelativistic Hamiltonian explicitly depends on the mass of the nucleus, the recoil corrections up to the order of α^{2} are automatically accounted for in the fine-structure calculations. Furthermore, the off-diagonal corrections to the fine structure (∼α^{4}) are estimated using the multireference methods based on one-electron Gaussian orbitals. The results obtained in this paper are considerably more accurate than those available in the literature. Moreover, we report accurate splittings for a number of excited ^{2}P^{o} states, for which there have been no reliable experimental or theoretical data at all. The calculated values presented in this paper may serve as a valuable guide for future experimental measurements of the fine structure of the boron atom. As the fine structure of an atom provides a spectral signature that can facilitate atom's detection, our data can also aid the search for trace amounts of boron in the interstellar medium.